Energy Supply Chains and Change - Diane J. Graziano; Elisa Alonso; Fletcher Fields; Diana Bauer (The Journal of Critical Infrastructure Policy, 2020)
The energy sector’s critical importance to the economy and national security on the one hand and its association with potential environmental impacts on the other subject it to competing and sometimes oscillating forces in policymaking and corporate decision-making that can affect both supply and demand. As such, energy supply chains need to be resilient in order to meet the economy’s dynamic demand for energy services, adapt to policy actions, respond effectively to natural and manmade disasters, foster transitions to emergent technologies, and serve long-lived infrastructure. This paper presents a framework that guides systematic analysis of energy supply chains subject to ongoing change. While the framework is qualitative, it is strengthened by quantitative data. A case study of the utility-scale gas turbine supply chain illustrates the framework.